2015
DOI: 10.1038/srep13796
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidences demonstrating differences in brain functions between nonmusicians and musicians

Abstract: Long-term music training can improve sensorimotor skills, as playing a musical instrument requires the functional integration of information related to multimodal sensory perception and motor execution. This functional integration often leads to functional reorganization of cerebral cortices, including auditory, visual, and motor areas. Moreover, music appreciation can modulate emotions (e.g., stress relief), and long-term music training can enhance a musician’s self-control and self-evaluation ability. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
1
7
0
1
Order By: Relevance
“…Electrophysiological indices might be more sensitive to subtle group differences than behavioral measures (e.g. Schön & François, 2011; see also Zhang, Peng, Chen, & Hu, 2015) and performance on stop-signal and Stroop tasks are not necessarily correlated and have been argued to reflect different underlying processes (e.g., Khng & Lee, 2014;MacLeod, Dodd, Sheard, Wilson, & Bibi, 2003). In fact, a previous study showing musician advantages on Stroop-type tasks (Bialystok & DePape, 2009) did not actually report smaller interference effects for musicians, but rather faster responses to both incongruent and congruent stimuli in a conflict context.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological indices might be more sensitive to subtle group differences than behavioral measures (e.g. Schön & François, 2011; see also Zhang, Peng, Chen, & Hu, 2015) and performance on stop-signal and Stroop tasks are not necessarily correlated and have been argued to reflect different underlying processes (e.g., Khng & Lee, 2014;MacLeod, Dodd, Sheard, Wilson, & Bibi, 2003). In fact, a previous study showing musician advantages on Stroop-type tasks (Bialystok & DePape, 2009) did not actually report smaller interference effects for musicians, but rather faster responses to both incongruent and congruent stimuli in a conflict context.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Alain et al (2007) reported finding smaller P2 amplitudes following training using speech sounds. More recently, Zhang et al (2015) also recorded smaller N1-P2 responses from musicians compared to non-musicians when they used click trains as the stimulus for evoked potential testing.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, brain signals were recorded using an EEG headset while the subject listens to music [44,53,58,100,110,112,115,116,151,154,190,205,216,220,222,235,276,279]. Moreover, the subjects' emotions were recognized as displayed by EEG signals.…”
Section: Domain Description Referencesmentioning
confidence: 99%